2007
DOI: 10.1007/s11095-007-9285-5
|View full text |Cite
|
Sign up to set email alerts
|

A Cheminformatic Toolkit for Mining Biomedical Knowledge

Abstract: This article will review cheminformatic tools that can be applied to facilitate annotation of PubChem through links to the scientific literature; to integrate PubChem with transcriptomic, proteomic, and metabolomic datasets; to incorporate results of numerical simulations of physiological systems into PubChem annotation; and ultimately, to translate data of chemical genomics screening efforts into information that will benefit biomedical researchers and physician scientists across all therapeutic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 192 publications
0
11
0
Order By: Relevance
“…The comprehensive information of small molecules and their biological activities in PubChem brings great opportunities for academic researchers in the chemical biology, medicinal chemistry and cheminformatics fields (Oprea et al ., 2007; Ovaa and van Leeuwen, 2008; Rosania et al ., 2007; Southan et al ., 2007) to access and utilize large scale biological activity data to meet their research goals. Several groups have attempted to develop methods to analyze the data in this database (Guha and Schurer, 2008; Han et al ., 2008; Hur and Wild, 2008; Nakai et al ., 2009; Xie and Chen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The comprehensive information of small molecules and their biological activities in PubChem brings great opportunities for academic researchers in the chemical biology, medicinal chemistry and cheminformatics fields (Oprea et al ., 2007; Ovaa and van Leeuwen, 2008; Rosania et al ., 2007; Southan et al ., 2007) to access and utilize large scale biological activity data to meet their research goals. Several groups have attempted to develop methods to analyze the data in this database (Guha and Schurer, 2008; Han et al ., 2008; Hur and Wild, 2008; Nakai et al ., 2009; Xie and Chen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These authors found that 32% of the GNF compounds could be linked to other databases by PubChem. Rosania et al reviewed the current cheminformatic tools available to mine biomedical knowledge, and the challenges involved to implement these tools for users who do not have extensive training in cheminformatics [8]. Ingsriswang and Pacharawongsakda developed a web based tool known as sMOL Explorer [9].…”
mentioning
confidence: 99%
“…Following advances in location proteomics 104108 , machine vision-based quantitative image analysis has been used to establish the degree of co-localization between compounds of interest with an organelle-specific reference marker 109111 . Furthermore, large combinatorial libraries of fluorescent probes and automated high content screening instruments have facilitated analysis of chemical motifs associated with specific intracellular distribution patterns 110112 . More recently, fluorescence resonance energy transfer has been used to study the trafficking and distribution of xenobiotics 113 .…”
Section: Whole Cell Based Microscopic Imaging Studies As Evidence Formentioning
confidence: 99%